Girls’ Stuff? Maternal Gender Stereotypes and Their Daughters’ Fear - Gerdes, Antje B. M.; Fraunfelter, Laura-Ashley; Braband, Melissa; Alpers, Georg W. (Frontiers in Psychology, 2022)
One of the most robust findings in psychopathology is the fact that specific phobias are more prevalent in women than in men. Although there are several theoretical accounts for biological and social contributions to this gender difference, empirical data is surprisingly limited. Interestingly, there is evidence that individuals with stereotypical feminine characteristics are more fearful than those with stereotypical masculine characteristics, this is beyond biological sex. Because gender role stereotypes are reinforced by parental behavior we aimed to examine the relationship of maternal gender stereotypes and children’s fear. Dyads of 38 mothers and their daughters (between age 6 and 10) were included. We assessed maternal implicit and explicit gender stereotypes as well as their daughters’ self-reported general fearfulness, specific fear of snakes, and approach behavior towards a living snake. First, mothers’ fear of snakes significantly correlated with their daughters’ fear of snakes. Second, mothers’ gender stereotypes significantly correlated with their daughters’ self-reported fear. Specifically, maternal implicit gender stereotypes were associated with daughters’ fear of snakes and fear ratings in response to the snake. Moreover, in children, self-reported fear correlated with avoidance of the fear-relevant animal. Together, these results provide first evidence for a potential role of parental gender stereotypes in the development and maintenance of fear in their offspring.